2019
DOI: 10.3329/jom.v20i2.42005
|View full text |Cite
|
Sign up to set email alerts
|

Etiological and Clinical Spectrum of Pancytopenia Based on Bone Marrow Examination

Abstract: Background: Bone marrow aspiration is assessed for cytology and trephine biopsy provides overall cellularity, detection of focal lesion and infiltration. Bone marrow study plays a crucial role in identifying cause of aplastic anaemia in clinical practice. This study was carried out to see the etiological and clinical spectrum of pancytopenia based on bone marrow examination. Materials and Methods: This descriptive study was conducted in the Department of Medicine, Dhaka medical college Hospital, Dhaka, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In India, numerous studies have highlighted megaloblastic anaemia and aplastic anaemia as the commonly encountered causes of pancytopenia. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Studies from neighbouring countries, including Pakistan, 16 , 17 , 18 , 19 , 20 Bangladesh 21 , 22 and Nepal, 23 , 24 , 25 show similar findings. Climate also affects the aetiology of pancytopenia by affecting disease transmission.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In India, numerous studies have highlighted megaloblastic anaemia and aplastic anaemia as the commonly encountered causes of pancytopenia. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Studies from neighbouring countries, including Pakistan, 16 , 17 , 18 , 19 , 20 Bangladesh 21 , 22 and Nepal, 23 , 24 , 25 show similar findings. Climate also affects the aetiology of pancytopenia by affecting disease transmission.…”
Section: Introductionmentioning
confidence: 75%
“…These parameters are comparable with other studies investigating the aetiology of pancytopenia. 6 , 7 , 14 , 15 , 16 , 21 , 45 , 46 …”
Section: Methodsmentioning
confidence: 99%
“…We also reported other etiologies like malaria, leishmaniasis, Salmonella, and HIV as infectious causes of pancytopenia. Other studies also reported malaria, visceral leishmaniasis, brucellosis, and sepsis as the common infections etiologies of pancytopenia [10,16]. This represents the wide spectrum of infectious etiologies of pancytopenia in children.…”
Section: Discussionmentioning
confidence: 90%